Dietary uridine improves lipid homeostasis in high-fat diet-induced obese mice by regulating liver gene expression and metabolomic profiles - Liu, Yilin; Zhang, Huihui; Yang, Xudong; Xie, Chunyan (Frontiers in Nutrition, 2025)
IntroductionObesity is caused by excessive storage of adipose tissue and leads to metabolic disorders. Uridine exerts modulatory effects on lipid metabolism, but the regulatory mechanism in obesity needs further research.MethodsIn this study, the effects of uridine supplementation on lipid metabolism were investigated in high-fat diet-induced obese mice. Mice aged at 8 weeks were randomly grouped to receive a control diet (CON, n = 10) or a high-fat diet (HF, n = 24). After 6 weeks of feeding, the HF group was further divided, with half receiving 0.4 mg/mL uridine supplementation in drinking water (HUR, n = 12) for an additional 4 weeks, while the remaining HF mice continued without intervention.ResultsThe results showed that the uridine supplement reduced the liver weight and intra-abdominal white adipose tissue weight in obese mice (p < 0.05). Treatment with uridine and free fatty acid resulted in a significant increase in late and total apoptosis, accompanied by a decrease in early apoptosis of mouse liver organoids (p < 0.05). Moreover, uridine lowered serum levels of triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), leptin, and liver TG content (p < 0.05). In obese mice fed with uridine, the expression of key genes involved in lipid transport [activated fatty acid translocase/cd36 (Fat/cd36) and low-density lipid receptor (Ldlr)], pyrimidine de novo synthesis [dihydroorotate dehydrogenase (Dhodh)], pyrimidine metabolism [uridine phosphorylase 2 (Upp2), ribonucleoside-diphosphate reductase subunit M2 (Rrm2), and thymidine kinase 1 (Tk1)] was improved (p < 0.05). Furthermore, liver metabolomic analysis identified 37 differential metabolites between the HF and HUR groups, primarily enriched in arachidonic acid metabolism and α-linolenic acid metabolism.DiscussionThese findings indicated that uridine supplementation can improve lipid metabolism in obese mice by regulating hepatic gene expression and metabolic pathways.